Measuring and Monitoring Adaptive Learning: A Landscape Review - LaFond, Anne; Adrian, Haley (USAID MOMENTUM Knowledge Accelerator, 2022)
This landscape review on measuring and monitoring adaptive learning hi ghlights the learning from five adaptive programming guidelines and to olkits and one implementation science framework to inform the monitori ng and evaluation of adaptive learning. The introduction of adaptive l earning processes and skillsets in global health programming is part o f an emerging strategy to advance a learning culture within projects a nd teams to improve health program performance. The monitoring and eva luation of adaptive learning is an emergent field aiming to monitor ho w adaptive learning processes have been introduced, how they are used, and whether they are having the intended results. Although there is a growing body of literature on adaptive programming more generally, th ere is a limited knowledge base on the monitoring and evaluation of ad aptive learning interventions and their impacts. Unlike other implemen tation strategies or program management approaches, there are no stand ard metrics or a monitoring and evaluation framework to track the inte gration, implementation, and effectiveness of adaptive learning in hea lth programming.